Histopathological characterisation of retinal lesions associated to Diplostomum species (Platyhelminthes: Trematoda) infection in polymorphic Arctic charr Salvelinus alpinus - Padrós, F.; Knudsen, R.; Blasco-Costa, I. (Zenodo, 2018)
Padrós, F., Knudsen, R., Blasco-Costa, I. (2018): Histopathological characterisation of retinal lesions associated to Diplostomum species (Platyhelminthes: Trematoda) infection in polymorphic Arctic charr Salvelinus alpinus. International Journal for Parasitology: Parasites and Wildlife 7 (1): 68-74, DOI:10.1016/j.ijppaw.2018.01.007, URL: http://dx.doi.org/10.1016/j.ijppaw.2018.01.007